The effectiveness of Carrefour house brand product strategy towards customer acceptance in Subang Jaya / Khairah Liyana Hassan - Hassan, Khairah Liyana (Faculty of Business and Management, 2008)
Carrefour is the world's second largest retailer, Carrefour SA operates more than 10,300 stores in France and abroad under more than two dozen names including Carrefour, Champion, Shopi, Marche Plus, Dia, Ed, and Promocash. The company merged with Promodes SA in 2000 to become Europe's leading operator of supermarkets, convenience stores, discount stores, cash-and-carry outlets, and hypermarkets. The company's founders created the concept of the hypermarket, an expanded supermarket offering a wide variety of merchandise-including groceries, electronics, clothing, and automotive supplies that allowed consumers to accomplish most of their shopping at one store. Hypermarkets became a rapid success, revolutionizing the retail industry in France and worldwide.